Explorando la comunidad lgbtiq+ en el entorno universitario - Espinoza Tejedor, Yustin Joel (Machala, 2023)
This research seeks to develop basic research through surveys, interviews to find out how many students are or identify with the LGBTIQ+ community, through a communication strategy such as an action plan implemented with the purpose of fulfilling the object of communication in something specific. Therefore, the general objective of this work is to analyze the importance of communication in the representation of the LGBTIQ+ community within the university environment. The methodology implemented is a mixed approach (qualitative and quantitative), and exploratory in nature. The purpose of this work is to promote improvements in the theory and for the results to be of great help to students and professionals who wish to investigate this topic and have information on how many students belong to or identify with the LGBTIQ+ community at the University.
La presente investigación busca desarrollar una investigación básica a través de encuestas, entrevistas para saber cuántos estudiantes son o se identifican con la comunidad LGBTIQ+, mediante estrategia comunicacionales como un plan de acción implementado con el propósito de cumplir el objeto de comunicación en algo específico. Por ello el objetivo general de este trabajo es analizar la importancia de la comunicación en la representación de la comunidad LGBTIQ+ dentro del entorno universitario. La metodología implementada es de enfoque mixto (cualitativo y cuantitativo), y de carácter exploratorio. Este trabajo tiene como propósito promover mejoras en la teoría y que los resultados sean de gran ayuda para los estudiantes y profesionales que deseen investigar acerca de este tema tengan información de cuántas estudiantes pertenecen o se identifican con la comunidad LGBTIQ+ en la Universidad.
Keywords: DIVERSIDAD SEXUAL; COMUNICACION Y REPRESENTACION; IDENTIDAD DE GENERO; COMUNIDAD LGBTIQ+